2013
DOI: 10.1590/s1415-47572013005000021
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in a world germplasm collection of tall fescue

Abstract: Festuca arundinacea Schreb., commonly known as tall fescue, is a major forage crop in temperate regions. Recently, a molecular analysis of different accessions of a world germplasm collection of tall fescue has demonstrated that it contains different species from the genus Festuca and allowed their rapid classification into the three major morphotypes (Continental, Mediterranean and Rhizomatous). In this study, we explored the genetic diversity of 161 accessions of Festuca species from 29 countries, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…In the present study, high number of SSR alleles per locus indicated a high significant allelic richness among the panel of accessions, at a mean of 11.16 alleles per locus (ranging from 3 to 26). The result was consistent with the study of Cuyeu et al 36 that detected 14.2 alleles per locus (ranging from 5 to 24) in 161 tall fescue by analyzing 15 polymorphic SSR markers. Tehrani et al 15 obtained a low mean of 5.9 polymorphic bands ranging from 2 to 11 alleles in analysis of 37 tall fescue individuals from Iran by 11 SSR markers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, high number of SSR alleles per locus indicated a high significant allelic richness among the panel of accessions, at a mean of 11.16 alleles per locus (ranging from 3 to 26). The result was consistent with the study of Cuyeu et al 36 that detected 14.2 alleles per locus (ranging from 5 to 24) in 161 tall fescue by analyzing 15 polymorphic SSR markers. Tehrani et al 15 obtained a low mean of 5.9 polymorphic bands ranging from 2 to 11 alleles in analysis of 37 tall fescue individuals from Iran by 11 SSR markers.…”
Section: Discussionsupporting
confidence: 92%
“…AMOVA suggested that 98.13% of the genetic variation resided among accessions within the population, with a statistically significant variance in heterogeneity within populations. Cuyeu et al 36 also revealed that 71% variance in 161 tall fescue accessions from 29 counties by 15 SSRs. The results indicated that tall fescue germplasm have a large diversity within the populations.…”
Section: Discussionmentioning
confidence: 95%
“…Rhizomatous tall fescue, named for its longer and more prevalent rhizomes, originated from the Iberian Peninsula but appears to be closely related to the Continental morphotype (Cuyeu et al, 2013;Hand et al, 2010). Three distinct morphotypes, Continental, Mediterranean, and rhizomatous (also known as races), have been described.…”
mentioning
confidence: 99%
“…Continental or summer-active tall fescue is prevalent in northern Europe and is the primary cultivated germplasm used as forage in temperate regions and widely adapted within the United States. Rhizomatous tall fescue, named for its longer and more prevalent rhizomes, originated from the Iberian Peninsula but appears to be closely related to the Continental morphotype (Cuyeu et al, 2013;Hand et al, 2010). Both Continental and rhizomatous tall fescue have hexaploid genomic constitutions (Hand et al, 2010.…”
mentioning
confidence: 99%
“…Tall fescue is a cross‐pollinated species possessing high levels of heterozygosity. Nearly all progeny are genetically unique, and substantial amounts of genetic variation occur both within (71%) and between (29%) populations (Cuyeu et al, 2013). Tall fescue, an allohexaploid (2 n = 6 x = 42), is part of a larger group of related plants that range from diploid (e.g., F. pratensis Huds.…”
mentioning
confidence: 99%